Kaartje dat ondertrouw en voornemen te trouwen op 31 juli 1919 van H, ploeg en A.C. Ploeg aankondigt
Kaartje dat ondertrouw en voornemen te trouwen op 31 juli 1919 van H, ploeg en A.C. Ploeg aankondigt.